The hound of the Baskervilles - Doyle, Arthur Conan (London: Puffin, 2011)
When Sir Charles Baskerville is found mysteriously dead in the grounds of Baskerville Hall, everyone remembers the legend of the monstrous creature that haunts the moor. The great detective Sherlock Holmes knows that there must be a more rational explanation, but the difficulty is to find it before the hellhound finds him
Keywords: Children's stories